Radical nanomedicine. (December 2006) - Rzigalinski, Beverly A; Meehan, Kathleen; Davis, Richey M; Xu, Yang; Miles, William C; Cohen, Courtney A
Nanotechnology has made significant advances in the reduction of free radical damage in the field of materials science. Cross-disciplinary interactions and the application of this technology to biological systems has led to the elucidation of novel nanoparticle antioxidants, which are the subject of this review. Recent reports suggest that cerium oxide and other nanoparticles are potent, and probably regenerative, free radical scavengers in  vitro and in  vivo. The neuroprotective, longevity-enhancing and anti-inflammatory properties of nanoparticles are summarized and hypotheses regarding their unique mechanism of action are presented. The chemical and physical properties of antioxidant nanoparticles are discussed in an interdisciplinary manner, with emphasis on biological properties and biomedical applications. Additionally, the need for alterations in traditional pharmacological parameters of dose and absorption, distribution, metabolism, and excretion are discussed and future directions necessary for bringing nanoparticle antioxidants into the realm of clinical reality are presented.